Preface to the special issues of the Twelfth European Wave and Tidal Energy Conference (EWTEC 2017) - A. W. Lewis (Chair, EWTEC 2017) (International Marine Energy Journal, 2018)
The twelfth conference of the European Wave and Tidal Energy Conference series was held at the verdant campus of University College Cork, Ireland, from Sunday 27th August to Saturday 1st September 2017. At EWTEC2017 the most up-to-date results from innovative research within both academia and industry were presented. The Conference had over 530 attendees from at least 25 countries, with the largest number of papers ever submitted to the proceedings and delivered through 336 oral presentations and 30 poster presentations over the four days.